Mechanisms for the Clinical Utility of Low‐Frequency Stimulation in Neuromodulation of the Dorsal Root Ganglion. Issue 4 (25th November 2020) - Chapman, Kenneth B.; Yousef, Tariq A.; Foster, Allison; D. Stanton‐Hicks, Michael; van Helmond, Noud
Abstract: Background: Dorsal root ganglion stimulation (DRG‐S) involves the electrical modulation of the somata of afferent neural fibers to treat chronic pain. DRG‐S has demonstrated clinical efficacy at frequencies lower than typically used with spinal cord stimulation (SCS). In a clinical study, we found that the frequency of DRG‐S can be tapered to a frequency as low as 4 Hz with no loss of efficacy. This review discusses possible mechanisms of action underlying effective pain relief with very low‐frequency DRG‐S. Materials and Methods: We performed a literature review to explore the role of frequency in neural transmission and the corresponding relevance of frequency settings with neuromodulation. Findings: Sensory neural transmission is a frequency‐modulated system, with signal frequency determining which mechanisms are activated in the dorsal horn. In the dorsal horn, low‐frequency signaling (<20 Hz) activates inhibitory processes while higher frequencies (>25 Hz) are excitatory. Physiologically, low‐threshold mechanoreceptors (LTMRs) fibers transmit or modulate innocuous mechanical touch at frequencies as low as 0.5–5 Hz, while nociceptive fibers transmit pain at high frequencies. We postulate that very low‐frequency DRG‐S, at least partially, harnesses LTMRs and the native endogenous opioid system. Utilizing lower stimulation frequency decreases the total energy delivery used for DRG‐S, extends battery life, and facilitates the development of devices with smaller generators.